Guaranteed Return to Work for White-Collar and Blue-Collar Workers: Impact of Covid-19 in Western and Eastern Indonesia : - Wise Harumi; Nasri Bachtiar; Neng Kamarni (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2022)
This study investigates the guaranteed recall likelihood of temporarily unemployed white-collar and blue-collar workers in the labour markets affected by Covid-19 in Indonesia’s western and eastern regions. The August 2020 microdata from Sakernas were used using logistic regression analysis. Descriptive analysis shows a balance of male and female workforce composition. However, the unemployment rate affected by Covid-19 is higher in western Indonesia than in eastern Indonesia. In the western part of Indonesia, the temporarily unemployed are more distributed in urban areas, while in the eastern part of Indonesia, they are more dispersed in rural areas. By gender, more men than women are temporarily unemployed due to Covid-19 in western and eastern Indonesia. Regression statistics show that layoffs and temporary layoffs impact white-collar and blue-collar workers differently. It can be seen that white-collar workers in western Indonesia have the highest return-to-work protection factor, while blue-collar workers in eastern Indonesia have the lowest. Urban areas provide blue-collar workers in eastern Indonesia with higher guaranteed chances of returning to work. Male white-collar workers in the Western Indonesia region are the most likely to return to work compared to other categories. The age variable is not significant for white-collar workers but is significant for blue-collar workers. The only significant education variable is the assurance that blue-collar workers in eastern Indonesia will return to work. An additional skill variant in the form of a course will provide a higher assurance of being recalled to work in the eastern region of Indonesia.